Triple Layer Synthetic Seed Encapsulation as An Alternative to In Vitro Culture of Kribo Orchid (Dendrobium spectabile) - Wiradanu, Farel Arkan; Nurrohmah, Aulia; Putri, Salsabila Tiara; Fadhilah, Said; Lu'lu'a, Aida Nisa (Agrosains : Jurnal Penelitian Agronomi, 2024)
Dendrobium spectabile is unique in that it has very diverse colors, shapes and sizes of flowers which make its market demand high but not commensurate with its production. The way to overcome this gap is with synthetic seed technology. The research design used was a completely randomized design with 2 factors, namely chitosan, which consisted of 5 levels, namely 0.05; 0.1; 0.15; 0.2% as well as control and betel leaf extract consisting of 4 levels, namely control; 1; 2; and 3%. Synthetic seeds are made with an Alginate concentration of 2.5%, starting with encapsulation and then providing chitosan soaking treatment and betel leaf extract according to the treatment. Observations were made 1 week after treatment and 3 weeks after treatment. The results show that the three-layer synthetic seeds have the characteristics of being white, non-wrinkling and dense. The lowest percentage of contamination was found in the treatment (0% chitosan + 3% betel leaf), (0.1% chitosan + 0% betel leaf), (0.1% chitosan + 1% betel leaf), (0.1% chitosan + 0.1% betel leaf). betel 3%), (chitosan 0.2% + betel leaf 0%), chitosan 0.2% + betel leaf 2%) of 25%. The cause of contamination is the fungus Rhizoctonia sp. and Aspergillus sp.. The highest shoot growth rate was found in the 0.15% chitosan + 1% betel leaf treatment. The highest number of roots was found in the treatments (0.15% chitosan + 0% betel leaf) and (0.2% chitosan + 2% betel leaf). The longest root growth was found in the treatment (0.15% chitosan + 0% betel leaf).